Interfacial Tension Between Injecting Fluid And Reservoir Oil At Elevated Pressure And Temperature - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2007)
An important parameter of surfactant flooding in enhanced oil recovery (EOR) processes is the interfacial tension (IFT) reduction between the injecting fluid and the reservoir oil. To measure the IFT precisely and accurately at high pressure and temperature, Pendant Drop Apparatus had been set up. IFT between surfactant solution and reservoir oil have been investigated at several different pressure and temperature. The working pressure ranged from 0 psig up to 5000 psig, and the temperature varied from ambient condition to 80oC. The results indicated that the interfacial tension behavior of surfactant solution and reservoir oil was very unique characteristics as the pressure and temperature increase. However, some conclusion can be withdrawn from these experiments. Increasing pressure causes relatively minor change in IFT. On the other hand the rise of temperature tended to raise the IFT much more significant. Since the surfactant solution having unique behavior therefore it is recommended that IFT must be measured in laboratory at the reservoir condition before injecting in to a reservoir.